GLOBAL (NUTMEG IN SHELL) TRADING: TRADE AND INTEGRATION OF INTERNATIONAL MARKET - maswadi maswadi (AGROLAND The Agricultural Sciences Journal (e-Journal), 2021)
The role of nutmeg in traditional and international trade is very significant because it is able to supply around 60-75 percent of the world's market share needs. The government as one of the market players has a role in creating strategic agricultural product price stabilization, and while there are still weaknesses of the agribusiness structure prevailing in Indonesia, integration analysis is very important given the benefits of knowledge about market integration. Market integration is useful to facilitate monitoring of price changes and support government policies on price stabilization and predict prices in the domestic market. Analysis of the market integration of this research uses the Vector Autoregression (VAR) model in difference determined through data stationarity test. Meanwhile, to determine the impact of the response of each variable due to shock (impulse response analysis) and Variance Decomposition. This research has three equations in the VAR analysis model and the results are all significant. The benefit of this research is to help determine the forecast of nutmeg prices in the domestic market and the impact of the response of each variable due to shocks.